Analysis of Air Pollution Due to Cigarette Smoke in Public Spaces and Mitigation Efforts - Indasah, Indasah; Anis Ansyori; Takariningsih (Universitas STRADA Indonesia, 2022)
Background: Air pollution remains a significant public health concern, with cigarette smoke contributing substantially to the degradation of air quality in public spaces. Purpose: This study aimed to analyse the extent of air pollution caused by cigarette smoke and to evaluate the effectiveness of various mitigation efforts. Method: A mixed-methods approach was employed, combining quantitative measurements of particulate matter (PM2.5) levels in designated public areas with qualitative surveys assessing public perception and awareness of the issue. Results: The results indicate that areas with high foot traffic exhibit PM2.5 levels exceeding World Health Organization (WHO) guidelines by up to 40%. Furthermore, public awareness campaigns have shown promise in reducing smoking prevalence in these spaces. Conclusion: This study underscores the urgent need for comprehensive policies to regulate smoking in public areas to safeguard public health